PTFE crystallization mechanisms: Insight from calorimetric and dilatometric experiments. (10th April 2020) - Guenoun, Gabriel; Faou, Jean-Yvon; Régnier, Gilles; Schmitt, Nicolas; Roux, Stéphane
Abstract: PTFE presents an original secondary crystallization that appears to be independent of the primary one. The conjunction of differential scanning calorimetry and dilatometry experiments has offered complementary data to study both crystallization melted compacted powder and of recrystallized samples. The primary crystallization is responsible for the crystallinity content variation with the cooling rate. It preserves the anisotropy induced by previous compaction that can be observed by dilatometry. Conversely, the secondary crystallization appears to be instantaneous, reversible, kinetic-free and isotropic. It occurs over a wide temperature range between 250°C and 310°C. Graphical abstract: Highlights: Two independent crystallization mechanisms for PTFE are proposed. The rate-limited primary crystallization sets the final crystallinity content. It inherits from uniaxial pressing of an anisotropy revealed in dilatometry. In contrast, the secondary crystallization is instantaneous and fully reversible. The secondary crystallization appears to be isotropic.